The art of Avatar : James Cameron's epic adventure - Fitzpatrick, Lisa, author (New York : Abrams, 2009)
The Art of Avatar, the companion book to the epic 3-D action adventure, explores the developmental and conceptual art used by the creative team to create the original world of Avatar. Features over 100 exclusive full-color images including sketches, matte paintings, drawings, and film stills.